Fashion Sebagai Identitas Sosial bagi Mahasiswa Universitas Udayana - Vanny, Putriana Septy; Kebayantini, Ni Luh Nyoman; Suka Arjawa, I Gusti Putu Bagus (JURNAL ILMIAH SOSIOLOGI (SOROT), 2021)
The purpose of this research is to examine overall social identity among students in Udayana University students. There are a lot of lifestyle and culture which each students had, in this research also I analyze fashion as social identity in the daily life of students in Udayana University and the impacts itself. This research uses a qualitative approach and descriptive exploratory with Dramaturgy theory by Erving Goffman. The result showed that fashion made a social identity on students trough the support of role model, enviroment, trend, technology, and clothes. All of the things has impacts in life inside the campus, relationship with parents also family, and it has economy impact for students. Based on dramaturgi theory which is front stage and back stage, where each students has their own clear boundaries between those two things, wearing a proper fashion both in front stage and otherwise in back stage. Keywords: Fashion, Students, Social Identity, Lifestyle, Dramaturgy